Renormalized and Entropy Solutions of Tumor Growth Model with Nonlinear Acid Production - Lingeshwaran, Shangerganesh; Nallasamy, Deiva Mani; Shanmugasundaram, Karthikeyan (Mathematical Modelling and Analysis, 2017)
This paper establishes the existence of renormalized and entropy solutions for a system of nonlinear reaction-diffusion equations which describes the tumor growth along with acidification and interaction. Under the assumptions of L1 data and no growth conditions with zero Dirichlet boundary conditions, we prove the existence of renormalized and entropy solutions for the considered mathematical model.